COLLABORATIVE POLICY OF THE GOVERNMENT OF BATU CITY IN IMPROVING THE COMMUNITY'S ECONOMY THROUGH SUSTAINABLE TOURISM, APPLE PICKING GROWTH IN TULUNGREJO VILLAGE, BATU CITY - Reygina Marta Dewi; Ali Roziqin; Tri Sulistyaningsih; Mohammad Syahrul Gunawan (ITB AAS INDONESIA, 2022)
The purpose of this study was to determine the active role of the Batu city government in increasing sustainable tourism and to find out the impact experienced by the community in the ongoing process of apple picking agro-tourism in the village of Tulungrejo, Batu City. By using this type of qualitative research. Sources of data in the form of interviews, observation and documentation, then the data is analyzed using data reduction, data presentation and data verification / drawing conclusions. The result of this research is that the Government is aggressively promoting the potential for entertainment tourism and natural tourism owned by Batu City, the impact is that tourist visits are increasing, and the opportunities for increasing the number of visitors to pick are getting bigger. At this time the lowest opportunity factor is the factor of